Loxapine-Induced Priapism: A Case Report and Review of the Literature on Antipsychotic-Induced Priapism - Alexandra L. Dodd; Sunny Patel; David C. Fipps (Case Reports in Psychiatry)
In this case report, a patient with schizophrenia experienced recurrent priapism while undergoing treatment of acute psychosis. This necessitated a review of the emergent treatment of priapism and discussion of the difficulties in treating priapism in a patient with acute psychosis. Therefore, this case report explores multiple possible etiologies of priapism within the realm of psychiatric care, reviews the proposed mechanisms of medication-induced priapism, and considers the psychopharmacological concepts that pertain to antipsychotic selection in the context of antipsychotic-induced priapism.